Pelatihan Menulis Cerita Non Fiksi Pada Mahasiswa Program Studi PGMI STKIP Nurul Huda Sukaraja OKU Timur - Pratama, Shakti Abdillah; Fitriani, Herni; Anam, Saiful; Rifa’i, Muhamad Nanang (Jurnal Indonesia Mengabdi, 2021)
This non-fiction story writing training was carried out with the aim that students from the Srikaton village youth groups could improve their writing skills and understanding of studying news in social media and its application in their daily environment. The focus of the training on writing non-fiction stories for students among the youth groups in Srikaton village consists of active students on campuses in East OKU district such as: STIE, STIPER, STIT MU, STKIP Muhammadiyah, STIT NU Sumber Agung, STISIP Binamarta. The training will follow the protocol. health measures from the government such as setting a one meter seat apart, preparing a handwashing area, and using a mask. The benefits that participants can get from this activity are being able to create a non-fiction story and understand news on social media so that they are wiser in applying it in everyday life.